Ship-based Trackline Geophysical Data (MGD77) from the Amundsen Sea, Antarctica acquired during the Nathaniel B. Palmer expedition NBP1005 (2010) ... - Yager, Patricia (Interdisciplinary Earth Data Alliance (IEDA), 2013)
This data set was acquired with a ship-based Gravimeter and Subbottom Profiler during Nathaniel B. Palmer expedition NBP1005 conducted in 2010 (Chief Scientist: Dr. Patricia Yager). These data files are of MGD77 format and include Bathymetry, Gravity (Field and Free Air Anomaly) data that were processed during the cruise. Data were acquired as part of the project(s): ASPIRE (Amundsen Sea Polynya International Research Expedition), and funding was provided by NSF grant(s): ANT08-39069 ...